Remaking multilingualism : a translanguaging approach - Otcu-Grillman, Bahar; Borjian, Maryam; García, Ofelia (Bristol, UK ; Jackson, TN : Multilingual Matters, 2022)
"This book is both a collection of cutting-edge research in the areas of multilingualism, translanguaging and bilingual education, and a tribute to the research and influence of Ofelia García. It recognizes Ofelia García's contribution as both a scholar and friend, and her place at the centre of a movement dedicated to equality and inclusion"--
Introduction -- Re-Making Multilingualism -- Bilingual Pedagogies and Teacher Education -- Bilingual Community Education -- Language Policy and Language Ideologies -- Epilogue -- Afterword: A Brief History of Work and Play with Ofelia García / Jo Anne Kleifgen -- Appendix: A List of Ofelia García's Publications with Multilingual Matters / Bahar Otcu-Grillman.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on March 09, 2022).
eBooks on EBSCOhost
Keywords: Multilingualism; Education, Bilingual; Translanguaging (Linguistics); Multilinguisme; Translanguaging; LANGUAGE ARTS & DISCIPLINES / Linguistics / General; Education, Bilingual; Multilingualism; Translanguaging (Linguistics); Essay; essays; Essays; Festschriften; Essays; Festschriften; Essais